New resin bee species in the genus Mielkeanthidium Urban (Hymenoptera, Megachilinae) - Parizotto, Daniele R.; Urban, Danúncia (Zootaxa, 2011)
Three new species of Mielkeanthidium are described and illustrated: M. albertinoi sp. nov., M. dissimile sp. nov. and M. tucumanum sp. nov. Generic characters are discussed and a key to species of the genus is provided. Mielkeanthidium is reported for the first time from Argentina (Tucumán).